The prevalence of generalized and syndromic hypermobility in elite Australian dancers. (July 2018) - Chan, Cliffton; Hopper, Luke; Zhang, Feili; Pacey, Verity; Nicholson, Leslie L.
Abstract: Objectives: To determine the prevalence of Generalized Joint Hypermobility (GJH) and Joint Hypermobility Syndrome/Ehlers-Danlos Syndrome–Hypermobility Type (JHS/EDS-HT) among dancers using established validated measures. Design: Observational Cohort Study. Setting: Laboratory. Participants: 85 dancers from two dance institutions. Main Outcome Measures: GJH was determined using the Beighton score (cut-point ≥5/9) and the Lower Limb Assessment Scale (LLAS) (cut-point ≥7/12). Presence of JHS/EDS-HT was assessed using the Brighton and Villefranche criteria. Paired sample t -test was performed to compare LLAS side-to-side scores, and percentage disagreements calculated to determine differences between the two GJH and the two JHS/EDS-HT measures. Results: 72% of dancers met the Beighton cut-point for GJH, while 38% and 42% met the LLAS cut-point on the left and right respectively. The proportion of dancers identified with GJH was different when assessed using the Beighton compared to the left and right LLAS (both p < 0.001), a disagreement of 48% and 46% respectively, with Beighton classifying more participants as having GJH. The Villefranche identified more dancers with JHS/EDS-HT than the Brighton (84% vs 31%, p < 0.001), with 54% disagreement. Conclusions: High prevalence of generalized and syndromic hypermobility was found regardless of the criteria used. A higher Beighton cut-point, e.g. ≥6/9, to identify true GJH amongst dancers maybe warranted. Highlights: Dancers have a high prevalence of generalized joint hypermobility (GJH). Professional dancers demonstrated greater hypermobility on their right leg. The LLAS is superior to the Beighton score in assessing GJH in dancers. A ≥6/9 cut-point for GJH is recommended if using the Beighton score in dancers. Brighton and Villefranche criteria overestimate syndromic hypermobility prevalence.